Childhood lichen planus with nail involvement: a case - Oztaş, Pinar; Onder, Meltem; Ilter, Nilsel; Oztaş, Murat Orhan (The Turkish Journal of Pediatrics, 2003)
Childhood lichen planus is a very rare entity which is characterized by violaceous, scaly, flat-topped polygonal papules commonly involving the flexor aspects of the wrists and legs, and oral and genital mucous embranes. The incidence of lichen planus peaks between the ages of 30 and 60 years, where as children comprise only 2% to 3% of reported cases. We report a nine-year-old girl with widespread lichen planus, involving the nails, with no mucosal involvement and regressing after treatment with a starting dosage of 20 mg/day systemic flucortolon (Ultralan) therapy.